When Ecology Needs Economics and Economics Needs Ecology: Interdisciplinary Exchange during the Anthropocene. Issue 2 (3rd May 2020) - Inkpen, S. Andrew; DesRoches, C. Tyler
ABSTRACT: Evidence that humans play a dominant role in most ecosystems forces scientists to confront systems that contain factors transgressing traditional disciplinary boundaries. However, it is an open question whether this state of affairs should encourage interdisciplinary exchange or integration. With two case studies, we show that exchange between ecologists and economists is preferable, for epistemological and policy-oriented reasons, to their acting independently. We call this "exchange gain." Our case studies show that theoretical exchanges can be less disruptive to current theory than commonly thought. Valuable interdisciplinary exchange does not necessarily require disciplinary breakdown.